1998
DOI: 10.1007/s002510050411
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of expression of the human lymphocyte activation gene-3 ( LAG-3 ) molecule, a ligand for MHC class II

Abstract: The lymphocyte activation gene-3 (LAG-3), a major histocompatibility complex (MHC) class II ligand evolutionarily related to CD4, is expressed exclusively in activated T and NK lymphocytes and seems to play a role in regulating the evolving immune response. We first determined that surface LAG-3 expression on activated human T cells is upregulated by certain cytokines (IL-2, IL-7, IL-12) and not by others (IL-4, IL-6, IL-10, TNF-alpha, TNF-beta, IFN-gamma). Surface LAG-3 expression correlated with intracellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 32 publications
1
56
0
Order By: Relevance
“…LAG3, a ligand for MHC class II receptors, is closely related to CD4 and downregulates the activated T-cells on which it is expressed through a high-affinity interaction with its receptor; this interaction blocks the binding of CD4 (ref. 24). Studies in LAG3 knockout mice have shown that LAG3 negatively regulates both the expansion of T-cells and the size of the memory-T-cell pool 25 .…”
Section: Discussionmentioning
confidence: 99%
“…LAG3, a ligand for MHC class II receptors, is closely related to CD4 and downregulates the activated T-cells on which it is expressed through a high-affinity interaction with its receptor; this interaction blocks the binding of CD4 (ref. 24). Studies in LAG3 knockout mice have shown that LAG3 negatively regulates both the expansion of T-cells and the size of the memory-T-cell pool 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Surface LAG-3 expression on activated human T cells is upregulated by interleukin IL-2, IL-7, and IL-12 and thus may play an essential role during activation. 41 LAG-3 has been associated as an inhibitory marker and in immune suppression. 3,8,9,11,15,16,42,43 Given the similarities in downstream targets, it is tempting to speculate that inhibitory molecules may act antagonistically against other positive costimulation.…”
Section: Discussionmentioning
confidence: 99%
“…LAG3 (CD223) was identified in 1990 by authors Triebel et al This surface protein is related to CD4 molecule and physiologically expressed on T-cells and natural killer-cells after cell activation and not on resting peripheral blood lymphocytes. 31 Surface LAG3 expression on activated human T-cells is up-regulated by interleukin IL-2, IL-7, and IL-12, 32 and is detectable on all human T-cells 2 to 3 days after activation. 33 Therefore LAG3 probably does not take part in induction phase of immune response but may play essential role during activation.…”
Section: Discussionmentioning
confidence: 99%